A new genus of nemonychid weevil from Burmese amber (Coleoptera, Curculionoidea) - Steve Davis (ZooKeys, 2014)
The first fossil nemonychid (Nemonychidae) in Burmese amber, belonging to the subfamily Rhinorhynchinae, is described and figured as Burmonyx zigrasi Davis and Engel, gen. n. and sp. n. While this specimen also comprises the first definitive record of the subfamily in the Asian continent, other compression fossils exist at least from the Yixian Formation of China and the Karatau site of Kazakhstan which may also deserve placement within this group. Although several important areas of the body are obscured by the shape and fragmented condition of the amber piece, a sufficient number of features are visible to consider adequate placement within Rhinorhynchinae, including the fairly strongly punctate elytral striae and appendiculate, nearly bifid pretarsal claws.